Enacting learning citizenship: a sociomaterial analysis of reflectivity and knowledge negotiation in higher education. Issue 5 (3rd September 2018) - Acton, Renae; Halbert, Kelsey
ABSTRACT: Across international university contexts, on-campus physical learning spaces are increasingly implemented with the aim of fostering active, collaborative, and student-centred learning. This paper theorises learning environments as complex sociomaterial assemblages of pedagogic approaches, material spaces and technologies, teachers, and learners that shift and flow in synergy to enact and refine students' dispositions for reflective practice. The article presents data from pre-service teachers and teacher educators as part of a broader case study investigating the pedagogic enactment of an innovative learning space in a regional Australian university. Sociomaterial studies of learning spaces are under-represented in understanding reflective practice. Staff and student narratives of practice illustrate processes of negotiating meaning and critical reflection within an embodied learning community. The findings illustrate the ways both social and material actors work in conjunction to enable learners' knowledge negotiation and reflective practices, and foster the dispositions and skills important for collaborative active citizenship.